Making Safeguarding Personal: progress of English local authorities. Issue 1 (12th February 2018) - Briggs, Mike; Cooper, Adi
Abstract : Purpose: The paper reports on the findings of a survey of 115 (76 per cent) of English local authorities in 2016 which compared progress on the implementation of the Making Safeguarding Personal (MSP) approach in local authorities through their Adult Social Care departments and in relation to their area Safeguarding Adults Boards (SABs) and partner organisations. The purpose of this paper is to evaluate the survey in relation to personalised social care and its impact on organisations, their staff and service users, and conclude with wider implications and recommendations for further work. Design/methodology/approach: A series of guided interviews were conducted with safeguarding leads from a sample comprising of 115 (76 per cent) of English local authorities during May and June 2016. The sample was randomly picked and balanced to give a fair representation of the different types of councils. The interviews were conducted by a team of five people. All interviewers had in-depth experience of adult safeguarding and were currently practicing independent chairs of SABs. The interviewers followed a prepared schedule consisting of a mixture of open and closed questions. All interviews were held over the phone and averaged one-hour duration. Findings: The results pointed to the impression that the majority of local authorities had completed the first step of introducing MSP, i.e. they had trained their workers and modified their systems. Most local authorities were moving into the next phase of embedding user-focussed work into their practice and culture, and were at various points along that journey. However, most had still to engage partner organisations beyond a mere acceptance of MSP as "a good thing". Research limitations/implications: The research has wide ranging implications for organisations and their workers in the field of adult safeguarding based on its findings. Its limitations are that only organisational leaders and managers were interviewed, although reference is extensively made to initiatives that engage service users. The authors acknowledged the possible bias of interviewees when judging the performance of their own service and attempted to moderate their views in the final report. Practical implications: The report references many practical implications to improve the practice of adult safeguarding in an attempt to make it more person-centred. Examples of good practice are given and recommendations are made to organisations. Social implications: It is recognised that there are many people who may be at risk of harm through their environmental, personal, age or disability-related situations. In improving the way that services respond to their needs, they will be made to feel safer and their lives enhanced. Originality/value: This original research follows up previous research in the preceding year. It is the widest ranging in its coverage of 76 per cent of English local authorities. Its value is that it measures progress towards full implementation of MSP; reports information and views from safeguarding leaders; and makes 20 recommendations to improve the implementation of MSP within local authorities, SABs and their partners.